2011
DOI: 10.4141/cjps09112
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci analysis of economically important traits inSorghum bicolor×S. sudanensehybrid

Abstract: Lu, X-p., Yun, J-f., Gao, C-p. and Acharya, S. 2011. Quantitative trait loci analysis of economically important traits in Sorghum bicolor×S. sudanense hybrid. Can. J. Plant Sci. 91: 81–90. Many agronomic traits of Sorghum bicolor×S. sudanense hybrid are quantitatively inherited, and the gene mapping of these traits has important research and practical consequences. In this study, genetic mapping and quantitative trait loci (QTL) analyses were conducted using 248 F2:3 plants of a cross between sorghum 314A (fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…However, QTL colocalization between leaf traits is often lacking or limited, as observed in the current study. QTL correspondence was completely lacking in perennial ryegrass (Yamada et al 2004), centipedegrass (Wang et al 2014), sorghum (Lu et al 2011), and Brachiaria (Thaikua et al 2016), while few colocalized QTL were reported in rice (Cai et al 2015; Liu et al 2015; Wang et al 2012; Yan et al 1999; Zhang et al 2015a) and wheat (Wu et al 2016). In a maize nested association mapping (NAM) population, leaf length and width displayed weak correlations and largely discrete putative causative variants underlying the traits (Tian et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, QTL colocalization between leaf traits is often lacking or limited, as observed in the current study. QTL correspondence was completely lacking in perennial ryegrass (Yamada et al 2004), centipedegrass (Wang et al 2014), sorghum (Lu et al 2011), and Brachiaria (Thaikua et al 2016), while few colocalized QTL were reported in rice (Cai et al 2015; Liu et al 2015; Wang et al 2012; Yan et al 1999; Zhang et al 2015a) and wheat (Wu et al 2016). In a maize nested association mapping (NAM) population, leaf length and width displayed weak correlations and largely discrete putative causative variants underlying the traits (Tian et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Sorghum genotypes with opaque white leaf midribs were reported to have drier, “pithy” stems, whereas genotypes with green midribs had stems with low levels of aerenchyma that accumulated higher amounts of sugars postflowering. More recent research identified QTL that modulate sorghum leaf midrib color and stem moisture content (Burks et al., ; Guan et al., ; Han et al., ; Hart et al., ; Mocoeur et al., ; Srinivas et al., ; Xiao‐ping et al., ; Xu et al., ). In the current study, a main effect QTL on SBI06 was identified in three populations that have a large impact on the accumulation of stem aerenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Stem volume, juiciness, and sugar concentration have been under selection in sweet sorghum in order to maximize sugar yield (Burks, Kaiser, Hawkins, & Brown, 2015;Carvalho & Rooney, 2017;Murray et al, 2008). Traits and QTL that modulate the accumulation of stem sugars have been identified (Burks et al, 2015;Felderhoff et al, 2012;Guan et al, 2011;Han et al, 2015;Hart, Schertz, Peng, & Syed, 2001;Mocoeur et al, 2015;Murray et al, 2008;Shiringani, Frisch, & Friedt, 2010;Srinivas et al, 2009;Xiao-ping, Jin-feng, Cui-ping, & Acharya, 2011), and the biochemical and molecular basis of stem sugar accumulation has been investigated (Calviño, Bruggmann, & Messing, 2008;Gutjahr et al, 2013;Lingle, 1987;McKinley et al, 2016;Milne et al, 2017). The stems of sorghum genotypes that accumulate high levels of sucrose generally lack or accumulate low levels of aerenchyma and maintain functional pith parenchyma with large vacuoles where sucrose is sequestered (Burks et al, 2015;Carvalho & Rooney, 2017;Hilson, 1916).…”
Section: )mentioning
confidence: 99%
“…This can serve as an important resource to improve carbon assimilation efficiency through breeding programs. Other QTLs of agronomic importance are those associated with main culm height [183], culm length, width and number [184], number of nodes [185], and stem diameter [132, 185, 186]. …”
Section: Qtls and Genes Governing Biofuel-related Traitsmentioning
confidence: 99%